CERITA HIDUP BERSIH: PENGETAHUAN PERILAKU HIDUP BERSIH DAN SEHAT YANG MENYENANGKAN UNTUK ANAK PAUD AL-GUFRAN BERSAMA MAHASISWA KKN WAIHAONG ANGKATAN L - Talib, Taufan; Samsuri, Diah Faradila; Wulandari, Megawati Putri; Keliangin, Maimuna; Pakay, Gita Febriani; Lattan, Kezia Ramona; Day, Aprilia; Boinauw, Zaenab; Narahubun, Albertina; Rumbaru, Musri; Koedoeboen, Filda; Robiwala, Emiliana; Solissa, Welmi (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2024)
Clean and healthy living behavior has a central role in shaping the foundation of early childhood health (PAUD), therefore we feel that knowledge about clean and healthy living behavior (PHBS) for early childhood needs to be educated in everyday life. For this reason, in this community service, we KKN students conducted a socialization of clean and healthy living behavior in one of the pre-schools in the Waihaong Ambon village, Paud Al-Gufran. In the implementation of this socialization we used fun methods with storytelling and singing techniques. The application of the method in the implementation of this socialization is the delivery of material by presenting a dongen story entitled "The Importance of Washing Hands" and teaching the steps of washing hands properly and correctly with song guidance. The results of the activities carried out to form the foundation of students' knowledge about clean and healthy living behavior in the school environment, and they have also been able to do 6 steps of good and correct hand washing according to WHO.